Consciousness-raising tasks for the mediation of text structure, cohesion, and coherence in essay writing - Rojas Vargas, Ana Lucía (Universidad de Costa Rica, 2020)
Several studies have demonstrated the positive impact of Consciousness-Raising tasks (CRTs) on the teaching of grammar, especially in foreign or second language learning. However, few studies have examined their effectiveness for the development of writing skills. With this in mind, the goal of this project is to explore the impact of CRTs on three aspects of writing in expository essays: text structure, cohesion, and coherence. To accomplish this goal, the study followed a mixed-method approach with a component of Classroom Action Research. The study was conducted in an English as Foreign Language class with a group of 12 eleventh-grade students at the International Baccalaureate Program at Palmares Bilingual High school, in Alajuela, Costa Rica. The data consisted of two sets of essays, classroom observations, and questionnaires to the students and the cooperating teacher. After comparing results from the first and second essays, the most noticeable improvement in the students’ writing was in text structure and cohesion, whereas coherence showed the lowest improvement. This points to a limitation of CRTs for addressing aspects of writing involving a larger number of rules and more abstract concepts, such as coherence, instead of a smaller number of rules, like cohesion. In conclusion, the authors suggest enquiring about the use of CRTs with simple topics involving decisions tied to explicit rules versus more complex topics involving abstract thinking and decisions not always linked to rules. Lastly, the authors recommend exploring strategies to make consciousness-raising a collaborative process as a way to mitigate task complexity